Elastic Bands or Gym Equipment for the Training of Older Adults? [¿Bandas Elásticas O Equipos de Gimnasio Para el Entrenamiento de Adultos Mayores?] - Herrera-Valenzuela, T (Federacion Espanola de Docentes de Educacion Fisica, 2019)
The aim of the present study was to compare the effects of six weeks of resistance training with the use of elastic bands (EB) to the use of traditional gym equipment (TGE) on maximum strength, body composition, manual grip, blood pressure, glycemia blood, agility, dynamic balance, flexibility, and peak aerobic consumption in older adults. This is an experimental study that evaluated two groups of older adults, one with EB (n=7) and another with TGE (n=5). A significant increase in maximal strength (EB: p=0.043 and TGE: p=0.018), peak aerobic consumption (EB: p=0.008 and TGE: p=0.038) and lower train flexibility (EB: p=0.021 and TGE: p=0.027), and a decrease of fat mass (EB: p=0.028 and TGE: p=0.021) were found. In conclusion, both training produce similar effects on neuromuscular, anthropometric, and metabolic variables in older adults. Therefore, using EB showed as effective as ETG in the training of older adults. © Federación Española de Asociaciones de Docentes de Educación Física (FEADEF) ISSN: Edición impresa: 1579-1726. Edición Web: 1988-2041 (www.retos.org)